THE The Influence Of Managerial Ownership, Debt Policy And Investment Decisions On The Value Of Construction Sector Companies Listed On The Bei For The 2018-2022 Period - Lestari, Indah Putri; Suhasto, Iwan Noor; Cahyaningdyah, Permatasari (Summa : Journal of Accounting and Tax, 2024)
Construction is one of the sectors contributing to Indonesia's GDP. Since the 2015 period, the construction sector has contributed around 9.94 percent of Indonesia's entire GDP. The purpose of this observation is to understand the effects of labor shortages, labor laws, and investment decisions on construction company numbers. In this case, asset quality is measured by asset quality (KM), the debt to equity ratio (DER) is used to measure debt, the price earnings ratio (PER) is used to measure investment intentions, and the price to book ratio (PBV) is used to measure intentions. invest. used to evaluate company figures. This observation uses a quantitative observation methodology. Using purposive sampling as a sampling technique, this observation involved samples from 20 construction companies in Indonesia between the period 2018 and 2022. The hypothesis was tested using multiple line regression using the SPSS statistical application. Observation findings show that, in partial terms, managerial quality has a negative effect on construction industry income. On the other hand , construction industry revenues are not negatively affected by labor laws or investment decisions. However, the results of simultaneous analysis of managerial personnel, building conditions, and investment decisions have a negative influence on construction company revenues.